2017
DOI: 10.1007/s12020-016-1220-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors, and outcomes of steroid-induced hyperglycemia in hospitalized patients with hematologic malignancies

Abstract: To determine prevalence, predictors, and outcomes of steroid-induced hyperglycemia in hospitalized patients with hematologic malignancies METHODS: We performed retrospective analysis of patients who were hospitalized on any of the four hematology services or bone marrow transplant service and who received systemic steroids during a 2-month period. Mean glucoses for days 1-4 and maximum glucose were calculated and the total daily steroid dose was converted to equivalent dose of dexamethasone. Hyperglycemia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Indeed, post-prandial capillary hyperglycemia had an incidence of 15.6%, which added to diabetes and prediabetes led the incidence of SIDM among hematologic patients to nearly 50% [28]. Recently, in a cohort of patients with hematologic malignancies requiring frequent, high-dose corticosteroids, hyperglycemia has been described with a prevalence of 39% [29].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, post-prandial capillary hyperglycemia had an incidence of 15.6%, which added to diabetes and prediabetes led the incidence of SIDM among hematologic patients to nearly 50% [28]. Recently, in a cohort of patients with hematologic malignancies requiring frequent, high-dose corticosteroids, hyperglycemia has been described with a prevalence of 39% [29].…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, glucose monitoring across the first 48 hours is very important in order to identify the most patients developing hyperglycemia, stopping further testing in case of absence of hyperglycemia within the first 48 hours [37]. Table 2 summarizes epidemiological data divided by different conditions according to main recent studies published within 2015 and 2018 [29,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Our population may have been at increased risk with 26% being of Black African or Caribbean ethnicity, a mean age of 58.6 years and a mean BMI of 27.7 kg/m 2 . In addition, the steroid doses were high, a factor directly correlated with risk of SID [8] , [9] . However this is similar to the incidence of SID in people with haematological malignancies reported previously [4] , [5] , [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of glucocorticoids in the setting of COVID-19 has been intensely debated, recent clinical trials have provided supportive evidence for their use in severe cases [3] , [4] . Steroid-induced hyperglycemia is a common metabolic side effect of glucocorticoid treatment in hospitalized patients with and without pre-existing diabetes [5] , [6] . It is reported that 20%–50% of patients without a previous history of diabetes show hyperglycemia after steroid administration [7] , [8] , [9] .…”
mentioning
confidence: 99%